Impaired tissue homing by the Ikzf3N159S variant is mediated by interfering with Ikaros function - Chang, Jingjie; Yamashita, Motoi; Padhi, Aditya K.; Zhang, Kam Y. J.; Taniuchi, Ichiro (Frontiers in Immunology, 2023)
AIOLOS, encoded by IKZF3, is a member of the IKZF family of proteins that plays an important role in regulating late B-cell differentiation. Human individuals heterozygous for the AIOLOS p.N160S variant displayed impaired humoral immune responses as well as impaired B and T cell development. We have previously reported that a mouse strain harboring an Ikzf3 N159S allele that corresponds to human IKZF3 N160S recapitulated immune-deficient phenotypes, such as impaired B cell development and loss of CD23 expression. In this study, we investigated the effect of the Ikzf3 N159S variant and found that B1a cell development was impaired in Ikzf3 N159S/N159S mice. In addition, CD62L expression was severely decreased in both B and T lymphocytes by the Ikzf3 N159S mutation, in a dose-dependent manner. Mixed bone marrow chimera experiments have revealed that most immunodeficient phenotypes, including low CD62L expression, occur in intrinsic cells.Interestingly, while Ikzf3 N159S/N159S lymphocytes were still present in the spleen, they were completely outcompeted by control cells in the lymph nodes, suggesting that the capacity for homing or retention in the lymph nodes was lost due to the Ikzf3 N159S mutation. The homing assay confirmed severely decreased homing abilities to lymph nodes of Ikzf3 N159S/N159S B and T lymphocytes but selective enrichment of CD62L expressing Ikzf3 N159S/N159S lymphocytes in lymph nodes. This finding suggests that impaired CD62L expression is the major reason for the impaired homing capacity caused by the Ikzf3 N159S mutation. Interestingly, an excess amount of Ikaros, but not Aiolos, restored CD62L expression in Ikzf3 N159S/N159S B cells. Together with the loss of CD62L expression due to Ikaros deficiency, the Aiolos N159S mutant protein likely interferes with Ikaros function through heterodimerization, at least in activating the Sell gene encoding CD62L expression. Thus, our results revealed that Aiolos N159S causes some immunodeficient phenotypes via the pathogenesis referred to as the heterodimeric interference as observed for Aiolos G158R variant.